HBR's 10 Must Reads on Diversity - Review, Harvard; Thomas, David; Ely, Robin; Hewlett, Sylvia; Williams, Joan (Ascent Audio, 2019)
Reap the benefits of a diverse workforce. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you create a culture that seeks and celebrates difference. This book will inspire you to: identify and address bias; short-circuit discrimination instead of unintentionally feeding it; attract, retain, and engage talented people who represent myriad identities; ensure that everyone has equal access to growth opportunities; trade outdated policies for practices that are proven to foster inclusion; and harness employees' unique skills and perspectives to transform how your company operates.